O-07 Improving access to financial support for individuals nearing the end of life. (19th November 2022) - Pikett, Emily
Abstract : Background: Fast-tracked access to financial support for those with less than 6 months to live was first introduced in 1990. In the following years, this process was applied to new benefits without any review (All-party Parliamentary Group for Terminal Illness, 2019). In 2019, an evaluation into this fast-tracked process was announced, with the intention of reviewing the criteria and improving implementation of this policy. Aims: Improve access to financial support for those nearing the end of life, regardless of their age or health condition; raise awareness of the financial support available for those nearing the end of life and their treating clinicians who provide medical evidence; integrate welfare support into the wider picture of health and social care. Methods: Evaluation – national survey of clinicians; comparison of international welfare systems; audit of medical evidence provided by clinicians to support fast-tracked claims; engagement sessions with clinicians, key medical organisations, end of life charities and individuals nearing the end of life or affected by terminal conditions; review of organisation's performance and process. Internal review of results culminated in new policy approach. Results: Legislation came into force on 4th April 2022 for two benefits to adopt a 12-month, end of life approach in place of the 6-month rule (The Universal Credit and Employment and Support Allowance (Terminal Illness) (Amendment) Regulations 2022). A Bill has been introduced to extend this change across the remaining benefits (Social Security (Special Rules for End of Life) Bill [HL] 2022-23). Guidance has been created for clinicians (Department for Work and Pensions, 2022), to support the provision of medical evidence whilst two sets of rules exist in the welfare system. Work continues to refine and optimise the fast-track application process. Conclusion: The adoption of the 12-month, end of life approach, aligns the welfare system with the definition of 'end of life' used in the NHS (NHS. What end of life care involves [Internet]; 2022). It is vital to use this opportunity to raise awareness across the palliative care community to ensure financial support is brought to mind when clinicians take a holistic approach to supporting patients who are nearing the end of life.